Method for assessing radon Re-Entrainment risks from above ground level discharges from sub-slab depressurization systems. (1st May 2022) - Lebel, Luke; Vu, Kim; John, Aneesh; Korolevych, Volodymyr
Abstract: Above ground level (ABL) discharges are commonly employed in northern climates to release radon-containing soil gases from sub-slab depressurization radon mitigation systems. While there are many practical reasons to employ this in cold climates (e.g., to avoid ice build-up), it does inherently elevate the outdoor radon concentrations, and raises the possibility of radon re-entrainment back into living spaces of the emitting house, and its neighbors. A method has been developed for assessing outdoor radon dispersion and re-entrainment risks. It links computational fluid dynamics calculations for evaluating outdoor concentrations, and regional multi-annual meteorological records that give the occurrence probability for different wind speed, wind direction, and atmospheric stability conditions. When combined with assumptions about indoor/outdoor concentration ratios, annual average exposure concentrations to radon can be estimated. Concentrations along surfaces of the emitting house are often quite high close to the exhaust vent, and air exchange into the house from nearby open windows, air intakes, etc., and can result in high indoor concentrations. Re-entrainment into the neighboring house is often less serious, though certain circumstances can lead to radon being trapped in the space between the two buildings, which leads to higher exposure. Highlights: CFD modeling of radon dispersion from above ground level exhausts. Combine with frequencies of prevailing wind conditions. Prevailing wind direction leads to formation of building cavities that traps radon. Method for assessing annual exposure for emitting building and neighbor.